Going Smokeless: Promotional Features and Reach of US Smokeless Tobacco Direct-Mail Advertising (July 2017–August 2018). Issue 8 (3rd December 2020) - Czaplicki, Lauren; Rahman, Basmah; Simpson, Randall; Rose, Shyanika W; Liu, Michael; Perks, Siobhan N; Moran, Meghan B; Schillo, Barbara A
Abstract: Introduction: Although cigarette use in the United States has declined over time, smokeless tobacco (SLT) use has remained steady. Direct-mail advertising and coupon redemption have been linked to increased tobacco use, and efforts to promote SLT through direct-mail advertising may contribute to sustained SLT use. We examined reach of SLT direct-mail advertisements by recipient demographics and promotional features, including coupons. Methods: Direct-mail data ( n = 418) were acquired from Comperemedia (Mintel) and coded for product type (traditional [eg, chewing tobacco], pouched [eg, moist snuff, snus], or both [traditional SLT and any pouched SLT products]); promotions (eg, coupons); flavors; and themes (eg, masculinity). Using Mintel's volume estimates for number of pieces sent, we calculated the proportion of mail volume sent by recipient demographics (age, income, region) and advertising features across product type. Results: Between July 2017 and August 2018, tobacco companies sent an estimated 249 million pieces of SLT direct-mail to US households; approximately half (49.6%) featured pouched SLT products. Across product types, over 75% of mail volume was sent to 31- to 60-year-old adults and 30–40% was sent to low-income households. The majority (>70%) of pouched SLT product mail contained coupons and flavor promotions. Outdoor and blue-collar-lifestyle themes were prominent in advertisements for all product types, along with less common adventure- and fun-related appeals. Conclusions: Coupons, flavors, and a combination of blue-collar and fun/adventure message themes were used to promote traditional and pouched SLT products through direct-mail, particularly to low-income households. Results support limits on direct-mail coupon distribution and continued surveillance of marketing appeals. Implications: There is a long history of research into tobacco advertising practices, largely focusing on cigarettes. This study highlights specific direct-mail marketing tactics used by the tobacco industry, including coupons to promote SLT products across the United States. Given the limited success in reducing SLT use and the association between direct-mail promotions and tobacco use, these study results provide support for policies to restrict use of coupons in direct-to-consumer tobacco marketing and indicate the need for continued surveillance of direct-mail advertisements as the SLT market continues to evolve.